Disarmament of micropollutants from wastewater using nylon waste/chitosan blended with algal biomass as recoverable membrane - Hanan B. Ahmed; Maher H. Helal; Mohamed H. Abdo; Medhat M. Fekry; Ahmed E. Abdelhamid (Polymer Testing, 2021)
In the current approach, a recoverable/bio-resistant membrane was innovatively prepared to be applicable in removal of Cu+2 and Pb+2 ions as water micropollutants. Nylon waste was currently exploited for removal of micropollutants, as low cost and ecofriendly alternative candidate for water treatment, i.e., ''waste treat waste''. Whereas, nylon waste was blended with chitosan to preliminary produce a polymer-polymer composite that could act as an effective physical barrier for water pollutants. Subsequentially, Nyl/Ch/Sarg membrane was produced by inclusion of micro-sized “Sargassum dentifolium” as non-living algal/costless bio-sorbent within nylon-chitosan composite, to be superiorly applicable in removal of water micropollutants, via adsorption-biosorption technique. Surface area was estimated to be 14.44 m2/g and swelling percentage was evaluated to be 45%for the prepared membrane. Porosity percentage was estimated to be 15% for nylon waste, and was significantly increased up to 28% for Nyl/Ch/Sarg membrane, meaning that, the porosity percentage was nearly duplicated. Nylon/chitosan composite showed to remove 28 mg/g of copper, however, after blending of algal biomass, the amount of copper removed was significantly increased up to 35.86 mg/g. Removal of the selected micropollutants was well-fitted to Freundlich modelling, while, KF was estimated to be 14.6 and 2.3 for lead and copper ions, respectively. Studying the recoverability showed that, even after 5 cycles the prepared membrane was capable for removal of 98% and 96% of Pb2+ and Cu2+ solutions, respectively. The bacterial colonization that affected on deterioration of nylon, was not affected on the morphological features of Nyl/Ch/Sarg membrane.